Evolution of the Arabidopsis telomerase RNA - Beilstein, Mark A.; Brinegar, Amy E.; Shippen, Dorothy E. (Frontiers in Genetics, 2012)
The telomerase reverse transcriptase promotes genome integrity by continually synthesizing a short telomere repeat sequence on chromosome ends. Telomerase is a ribonucleoprotein complex whose integral RNA subunit TER contains a template domain with a sequence complementary to the telomere repeat that is reiteratively copied by the catalytic subunit. Although TER harbors well-conserved secondary structure elements, its nucleotide sequence is highly divergent, even among closely related organisms. Thus, it has been extremely challenging to identify TER orthologs by bioinformatics strategies. Recently, TER was reported in the flowering plant, Arabidopsis thaliana. In contrast to other model organisms, A. thaliana encodes two TER subunits, only one of which is required to maintain telomere tracts in vivo. Here we investigate the evolution of TER in Arabidopsis and its close relatives. We employ a combination of PCR and bioinformatics approaches to identify TER loci based on syntenic regions flanking the TER1 and TER2 loci of A. thaliana. Unexpectedly, we discovered that the genomic regions encoding the two A. thaliana TERs occur as a single locus in other Brassicaceae. Moreover, we find striking sequence divergence within the telomere templating domain of TERs from Brassicaceae, including some orthologous loci that completely lack a template domain. Finally, evolution of the TER locus is characterized by lineage-specific events rather than changes shared among closely related species. We conclude that the TER duplication occurred very recently, and further that TER in Brassicaceae is evolving at an extraordinarily rapid pace.